Rome and the worlds beyond its frontiers - Slootjes, Daniëlle.; Peachin, Michael, 1954- (Impact of Empire, 2016)
This volume offers an expansive approach to interactions between Romans and those beyond the borders of Rome. The range of papers included here is wide, both in terms of subject matter and with respect to approach. That said, a number of important themes bind the essays. Who is an insider, and who the outsider? How were these categories of person, or identity, fashioned and/or recognized in antiquity? How shall we recognize them now? What are the categories, or standards, for measuring or determining inside and outside in the Roman world? And then, of course, what are the repercussions when inside and outside come into contact? What happens when the outside is in, or the inside out?